Effect of blood pH on pulmonary artery pressure, left atrial pressure and fluid filtration rate in isolated rabbit lung. (Revista Española de Fisiología, 1995)
To determine the effects of pH changes on Pulmonary Artery Pressure (PAP), 18 isolated rabbit lung preparations, perfused with autologous blood mixture and constant PaCO2 have been studied. Each preparation was studied under 3 conditions: Baseline: 30 minutes equilibration period. Acidosis: pH was decreased by 0.2 N HCl infusion, the ventilatory rate was changed and different CO2 mixtures were used to maintain the PCO2 within the initial parameters. Compensated Acidosis (CA): pH was returned to normal values by 0.7 N NaHCO3 infusion maintaining PCO2 in its initial values. The decrease in pH (acidosis) from 7.36 +/- 0.05 to 7.18 +/- 0.06 at constant PCO2, generated a significant increase in PAP (13.6 +/- 3.2 cm H2O to 18.8 +/- 5.2 cm H2O, p < 0.01). The pH increase (CA) from 7.18 +/- 0.06 to 7.40 +/- 0.09 caused the PAP to decrease (18.8 +/- 5.2 cm H2O to 15.9 +/- 4.2 cm H2O); the fluid filtration rate remained unchanged during the whole experiment. It is concluded that blood pH changes at constant PCO2 result in significant changes of PAP. Acidemia produces pulmonary vasoconstriction, which may be a contributing factor in the genesis of pulmonary hypertension in clinical conditions with increased hydrogen ion concentration [H+].